HLA-A*30:01 and HLA-A*33:03 are the protective alleles while HLA-A*01:01 serves as the susceptible gene for cervical cancer patients in Xinjiang, China - Alifu, M; Hu, Y; Dong, T; Wang, R (Medknow Publications, 2018)
Objective: This study aims to investigate the distribution of HLA-A genes and identify alleles related to cervical cancer. Materials and Methods: A total of 252 cervical cancer patients (56 Han ethnic and 196 Uyghur ethnic) and 213 controls (103 Han ethnic and 110 Uyghur ethnic) were recruited in this study. HLA-A alleles were examined by polymerase chain reaction with sequence-specific primers. The frequencies of different HLA-A alleles were compared between the two ethnic groups as well as patients and controls. The correlation of HLA-A frequencies with various clinical characteristics and short-term treatment efficacy was analyzed. Results: (1) Significantly higher frequencies of HLA-A*03:01 and HLA-A*03:02 and lower frequencies of HLA-A*11:01, HLA-A*24:02, and HLA-A*30:01 were observed in the Uyghur control groups than in Han control groups (P ≤ 0.05). (2) The frequency of HLA-A*01:01 in patients was significantly higher than controls. In contrast, the frequencies of HLA-A*30:01 and HLA-A*33:03 were lower in patients (P ≤ 0.05). (3) The frequency of HLA-A*30:01 in Han patients was lower than Han control group (P ≤ 0.05). However, there was no statistically significant in the frequency of HLA-A between Uyghur patients and controls (P > 0.05). (4) There was no significant association between HLA-A alleles and HPV16 or squamous cell carcinoma antigen levels (P > 0.05). (5) The frequency of HLA-A*30:01 allele in complete response + partial response group was higher than stable disease + progressive disease group (P ≤ 0.05). Conclusions: People from two ethnic groups displayed different HLA-A gene distribution. HLA-A*30:01 and HLA-A*33:03 alleles are the protective factors to cervical cancer patients from Xinjiang while HLA-A*01:01 serves as the susceptible gene.